Two new species of phytoseiid mites (Acari: Phytoseiidae) from Cameroon, Central Africa - Zannou, I.; Hanna, R.; Moraes, G.J. de; Zundel, C. (2005)
Two new mite species of the family Phytoseiidae (Acari: Mesostigmata), Neoseiulus yanineki sp.nov.and Typhlodromips cameroonensis sp. nov., are described from Cameroon, Central Africa.